Stigma of Sexual Violence and Women's Decision to Work - Tanika Chakraborty; Anirban Mukherjee; Swapnika Reddy Rachapalli; Sarani Saha (Institute of Labor Economics (IZA), 2017)
Our study is motivated by two disturbing evidences concerning women in India. On one hand, crime against women is on the rise while on the other, women's labor force participation rate (WLFPR) has been declining over the last three decades. We estimate the extent to which the decline in WLFPR can be assigned to increasing instances of crime against women. We argue that an increase in crime against women, increases the non-pecuniary costs of traveling to work, particularly in a traditional society marked by stigma against victims of sexual crimes. Our findings suggest that women are less likely to work away from home in regions where the perceived threat of sexual harassment against girls is higher. The estimate is robust to various sensitivity checks. Moreover, the deterrence effect of crime responds to the opportunity cost of work on one hand and the stigma cost of sexual crimes on the other.
Keywords: E24; J16; J18; 330; crime against women; labor force participation; stigma cost